2020
DOI: 10.21037/tcr-20-2359
|View full text |Cite
|
Sign up to set email alerts
|

Functions of polyphenols and its anticancer properties in biomedical research: a narrative review

Abstract: Cancer is a major health concern as the incidence is growing worldwide and still lacks successful therapies. Plant-derived functional foods are getting considerable attention, primarily due to their safety and therapeutic potential. Polyphenols are a group of mostly natural, water-soluble organic compounds.Here, we review the functions of selected polyphenols and their anticancer properties on numerous cancer cell lines and their mechanisms. The literature search was performed using the electronic database Pub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
59
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 103 publications
(64 citation statements)
references
References 85 publications
4
59
0
1
Order By: Relevance
“…Natural flavonoids have received considerable attention as substitutes for developing novel antineoplastic agents in recent years [ 17 ]. Polyphenols are a group of organic compounds involving flavonoids (e.g., flavanols, flavones, anthocyanins, isoflavonoids, flavonols, and flavanones) and nonflavonoids (e.g., xanthones, lignans, phenolic acids, tannins, and stilbenes) [ 18 ]. Flavonoids are secondary metabolites consisting of a benzopyrone ring with phenolic or poly-phenolic groups attached at different positions and are abundant in fruits, flowers, seeds, stems, cereals, nuts, vegetables, and herbs [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Natural flavonoids have received considerable attention as substitutes for developing novel antineoplastic agents in recent years [ 17 ]. Polyphenols are a group of organic compounds involving flavonoids (e.g., flavanols, flavones, anthocyanins, isoflavonoids, flavonols, and flavanones) and nonflavonoids (e.g., xanthones, lignans, phenolic acids, tannins, and stilbenes) [ 18 ]. Flavonoids are secondary metabolites consisting of a benzopyrone ring with phenolic or poly-phenolic groups attached at different positions and are abundant in fruits, flowers, seeds, stems, cereals, nuts, vegetables, and herbs [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…is antioxidant capacity of D. edulis led some authors to suggest that this plant may help in preventing oxidative damage associated with cancer [28]. A phytochemical assay we recently performed [4] with the aqueous extract of D. edulis leaves indicated the presence of a wide range of bioactive compounds (flavonoids, phenols, alkaloids, and flavonols) endowed with antiproliferative and anticancer activities [29]. In addition, this plant extract was reported to inhibit cell growth and proliferation induced by estradiol on the uterus and vagina of female Wistar rats [4], supporting in part the hypothesis according to which this plant may help against cancer diseases [28].…”
Section: Introductionmentioning
confidence: 99%
“…Natural products or their derivatives are promising alternatives for anti-cancer therapeutics. Some studies have confirmed that polyphenol-rich extracts from natural resources possess health benefits by delaying tumor onset [ 59 ]. The anticarcinogenic properties of these molecules are related with their capacity to inhibit cancer cell proliferation, angiogenesis, metastasis, apoptosis, and inflammation [ 60 ].…”
Section: Resultsmentioning
confidence: 99%